2022
DOI: 10.1210/endocr/bqac197
|View full text |Cite
|
Sign up to set email alerts
|

GABA Signaling in the Posterodorsal Medial Amygdala Mediates Stress-induced Suppression of LH Pulsatility in Female Mice

Abstract: Psychological stress is linked to infertility by suppressing the hypothalamic gonadotropin-releasing hormone (GnRH) pulse generator. The posterodorsal subnucleus of the medial amygdala (MePD) is an upstream regulator of GnRH pulse generator activity and displays increased neuronal activation during psychological stress. The MePD is primarily a GABAergic nucleus with a strong GABAergic projection to hypothalamic reproductive centres, however, their functional significance has not been determined. We hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…The discovery that activation of MePD kiss1 neurons increases the frequency of the GnRH pulse generator raised the hypothesis for the involvement of intranuclear GABA‐GABA disinhibitory interactions, typical of limbic pallidal structures, such as the MePD. Moreover, the MePD sends functional GABAergic projections to the ARC, 66 providing a possible route via which MePD kiss1 neurons modulate the activity of the GnRH pulse generator. Neuropharmacological studies aiming to untangle this functional neural circuitry in the MePD have demonstrated that GABA and glutamate neurotransmission within this region is necessary for kiss1 neurons to exert their upstream control over the GnRH pulse generator 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that activation of MePD kiss1 neurons increases the frequency of the GnRH pulse generator raised the hypothesis for the involvement of intranuclear GABA‐GABA disinhibitory interactions, typical of limbic pallidal structures, such as the MePD. Moreover, the MePD sends functional GABAergic projections to the ARC, 66 providing a possible route via which MePD kiss1 neurons modulate the activity of the GnRH pulse generator. Neuropharmacological studies aiming to untangle this functional neural circuitry in the MePD have demonstrated that GABA and glutamate neurotransmission within this region is necessary for kiss1 neurons to exert their upstream control over the GnRH pulse generator 38 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an ‘instructive’ component, i.e. GABA projections, provides a unique contribution that is imperative for the inhibitory effect of the MePD on reproductive function ( McIntyre et al, 2022 ). Balanced feed-forward excitation and feed-forward inhibition ensures that the overall excitability of the KNDy network is robust to the elevated excitatory input, permitting GABAergic projections to exert ‘inhibitory brake’, thus maintaining the LH IPI to prestimulation levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an 'instructive' component, i.e. GABA projections, provides a unique contribution that is imperative for the inhibitory effect of the MePD on reproductive function(McIntyre et al, 2022).…”
mentioning
confidence: 99%
“…Two recent Endocrinology papers from the O’Byrne lab ( 1 , 2 ) advance and elaborate the role of GABAergic and urocortin-3 neurons in the posterodorsal subnucleus of the medial amygdala (MePD) in mediating acute psychological stress-induced suppression of luteinizing hormone (LH) pulses, possibly via their projection to the hypothalamic gonadotropin-releasing hormone (GnRH) pulse generator. This group has already laid much of the groundwork to show that the MePD modulates pulsatile LH secretion ( 3 ) as well as pubertal timing.…”
mentioning
confidence: 99%
“…Others have provided evidence for direct projections from the amygdala to the kisspeptin neurons located in the arcuate nucleus (eg, 4 ), which are considered to be the hypothalamic GnRH/LH pulse generator. In the first of the 2 featured O’Byrne papers ( 1 ), McIntyre and colleagues show that MePD GABAergic neurons mediate stress-induced suppression of LH pulses in female mice. Two different experimental psychosocial stressors were used to reinforce their findings: restraint and exposure to the odor of 2,5-dihydro-2,4,5-trimethylthiazoline (a single molecule constituent of fox urine).…”
mentioning
confidence: 99%